Interaksi Manusia Dengan Alien Dan Peranan AI Dalam Novel Only Human Karya Sylvain Neuvel - Diky Ajie Andriana; Maksilino Devaldo Siletty; Eva Dwi Kurniawan (STIKes Ibnu Sina Ajibarang, 2024)
The science fiction novel